KONDISI MADRASAH TSANAWIYAH DAN MADRASAH ALIYAH DI KECAMATAN JEMAJA KABUPATEN KEPULAUAN ANAMBAS TAHUN 2008-2014 - Kardi Candra; Dra. Bedriati Ibrahim M.Si; Bunari M.Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Education is basically aims to lead the students toward behavioral changes both intellectually, morally, and socially. To be able to live independently as individuals and social beings so as to produce qualified human resources. Enterprises in order to achieve the educational goals of the school as an institution of formal education the only one who held the government plays an important role in realizing the goal of national education. This study aims to determine (1) the condition of the MTs and MA in District Jemaja Anambas Island 2008-2014. (2) To determine what factors are becoming shortage of teachers and students in the District Jemaja after the formation of the district. (3) To know what a given society dukangan District of Jemaja in the face of the MTs and MA condition that a shortage of teachers and pupils. (4) To find out how the settlement of teacher shortages that occurred in the District Jemaja Anambas Island 2008-2014. The method used in this research is the historical method and qualitative methods. Data were obtained from interviews and then analyzed in a language sendiri. This research locations are in the District of Jemaja regency Anambas Island. Time of research began on the proposal until the exam seminar Skripsi. Teknik used data collection techniques are observation, interview techniques, technical documentation and engineering studies library.Keywords: Education, School Conditions